Depositor Response to Risk of Local Development Banks: A Case of Indonesia - Erie Febrian (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
There have been some studies carried out to empirically show how depositor respond the magnitude of risk in various types of banks, in different economies. Some studies have also checked the issue when banks are protected by Deposit Insurance. Nevertheless, the aforementioned studies have never adequately covered the issue on local development banks. These financial institutions may not fulfill the necessary conditions of effective Discipline of the market, due to a high degree back up provided by the associated local government. This article is to cover the literature gap, i.e., by studying how depositors reply to risk magnitude of local development banks (known as BPD) in Indonesia. This research employs monthly data of ten BPDs with the largest asset operational in Indonesia, which is attained from the country’s Authority of Financial Service. We run analysis employing Reduced Form Formula. In this approach, the first model is to measure the risk of each bank employing Probit formula and data from 2014.1 to 2015.12. The results of this model are then employed as exogenouselement in the second phase model, Multiple Regression Formula. The second model utilizes data from 2016.1 to 2017.3 to show the response of bank customers to the risk of the observed financial institutions.